Methodological Approaches to Assessing the Level of Enterprise Risk Resistibility (Economics and region, 2019)
The analysis of scientific literature allowed us to systematize modern approaches to the interpretation of the category of «enterprise risk resistibility». Therefore, the article provides a comparative analysis of the categories «enterprise risk resistibility», «enterprise risk protection» and «enterprise economic security», their common features and differences are determined, proposed a three-level model of enterprise activity security. Since the level of enterprise risk resistibility is determined by the level of stability for each component, it is proposed to define the integral indicator of resistibility as a weighted average of indicators characterizing the current, tactical and strategic level of enterprise risk resistibility.
Keywords: risk; enterprise risk resistibility; components of enterprise risk resistibility; enterprise risk; resistibility index